Smart fire monitoring system with remote control usingZigBee network - Jung kyu Park; Jaeho Kim (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
There are several differences between the two types of alarm systems, conventionalsystems and addressable systems.  It is important to carefully determine the introduc-tion of a fire alarm system according to the installation environment.  Talking aboutthe main difference relates to how the connected device communicates with the maincontrol panel by sending a signal.  Cost is another factor that can be a determinant ofyour chosen fire alarm system. In this paper, we proposed smart addressable fire detec-tion system.  In the proposed system, IoT was used and the network was constructedusing ZigBee module.  In the configured network, it consists of a local server and acontrol server. The local server controls the addressing sensor and sends the informa-tion obtained from the sensor to the control server.  The control server receives datatransmitted from the local server and enables quick fire action.  In the actual imple-mentation, the local server used the Lycra controller and ZigBee module. In addition,the control server used the Raspberry Pi and ZigBee modules and connected to theEthernet so that the administrator could monitor or control the local server.